2018
DOI: 10.1111/his.13460
|View full text |Cite
|
Sign up to set email alerts
|

Gastric pyloric gland adenoma: a multicentre clinicopathological study of 67 cases

Abstract: The risk of HGD increases with the size of PGA, tubulovillous architecture and the presence of AIG as well as mixed immunophenotype. As the overall local recurrence rate is less than 10%, PGAs may be treated conservatively, but they should be excised completely if possible, particularly if they are large or show high-grade features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 21 publications
2
80
0
Order By: Relevance
“…In our series of 57 duodenal PGA we have shown that they typically arise in the proximal duodenum in older individuals, a minority of whom have adjacent gastric heterotopia. Larger lesions and those showing villous architecture within the lesion were more likely to harbour areas of high‐grade dysplasia or invasive malignancy, similar to the features of high‐grade lesions within the stomach …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our series of 57 duodenal PGA we have shown that they typically arise in the proximal duodenum in older individuals, a minority of whom have adjacent gastric heterotopia. Larger lesions and those showing villous architecture within the lesion were more likely to harbour areas of high‐grade dysplasia or invasive malignancy, similar to the features of high‐grade lesions within the stomach …”
Section: Discussionmentioning
confidence: 89%
“…Twenty‐seven had sufficient tissue to perform additional IHC stains for intestinal markers MUC2, CDX2 and CD10. The histological features of the PGA analysed were the architectural growth pattern and grade of dysplasia, as previously described . In short, architecture was broadly classified into cases with predominantly tubular growth or those with both tubular and villous (tubulovillous) growth patterns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of gastric adenoma and adenocarcinoma, low-grade adenoma/dysplasia showed stable intestinal phenotype and high-grade adenoma/dysplasia showed unstable gastric or mixed gastric and intestinal phenotype. 12,13 Furthermore, mixed immunophenotype of MU5AC and MUC6 has recently been demonstrated in HGD than in LGD of pyloric gland adenomas, 14 and the positive immunoreactivity of MUC6 is suggested to be a risk factor for malignant change. 15 Taken together, mixed immunophenotype may indicate unstableness and malignant potential of HGD.…”
Section: Discussionmentioning
confidence: 99%
“…Foveolar (17%) and pyloric gland type (3%) adenomas are more common in FAP than conventional adenomas. 25 Endoscopic management of these polyps, even those with superficial submucosal invasion, is usually adequate and gastrectomy is reserved for deeply infiltrating carcinomas.…”
Section: Familial Adenomatous Polyposis (Fap)mentioning
confidence: 99%